Think about space : where have we been and where are we going? - Asimov, Isaac, 1920-1992.; White, Frank, 1944- (New York, NY : Walker, 1989)
An overview of the history and present and future role of human beings in space tracing the development of space exploration and discussing the challenges of the present day and the possibilities of the future.
Includes bibliographical references (p. [113-114]) and index.
Booklist.
School Library Journal.
7.3
7.3
7-10.
Keywords: Space sciences -- Juvenile literature; Space sciences; Space sciences